Executive functioning in body dysmorphic disorder and obsessive–compulsive disorder. (27th February 2023) - Chen, Long Long; Flygare, Oskar; Wallert, John; Enander, Jesper; Ivanov, Volen Z.; Rück, Christian; Djurfeldt, Diana
Abstract: Objective: To assess executive functions (EFs) in patients with body dysmorphic disorder (BDD) and obsessive–compulsive disorder (OCD) compared with healthy controls. Methods: Adults diagnosed with BDD (n = 26) or OCD (n = 29) according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, and healthy controls (n = 28) underwent validated and computerized neuropsychological tests, spatial working memory (SWM), intra–extra-dimensional set shifting (IED), and stop signal task (SST), from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Test performance was compared between groups, and correlated with standardized symptom severity of BDD and OCD. Significance level was set to P  < .05. Results: There were no statistically significant between-group differences on key outcome measures in SWM, IED, or SST. There was a weak positive correlation between symptom severity and test errors on SWM and IED in both OCD and BDD groups; increased clinical severity was associated with more errors in these tests. Furthermore, there was a negative correlation between symptom severity and SST in the BDD group. Conclusions: Patients with BDD or OCD did not differ from healthy control subjects in terms of test performance; however, there were several statistically significant correlations between symptom severity and performance in those with BDD or OCD. More studies on EFs in BDD and OCD are required to elucidate if there are differences in EFs between these two disorders.